Global trends in information avoidance research: a bibliometric analysis - Ahmad, Shakil; Masrek, Mohamad Noorman; Wan Mokhtar, Wan Nor Haliza (Faculty of Information Management, 2025)
The topic of information avoidance has gained the attention of researchers in the fields of health and other disciplines. However, the bibliometric method has rarely been applied to analyze information avoidance research. This study aims to analyze the research published on information avoidance using bibliometric indicators. The source of data for this study is the Scopus database. The study examines the authors’ keywords, visualizes the thematic evolution, provides yearly growth of publications and citations, and identifies the highly cited papers and most productive countries, institutions, and authors. The study examines the current status of research and provides a reference for future research directions.